Comparative genetic stock structure in three species of commercially exploited Indo‐Malay Carangidae (Teleosteii, Perciformes). Issue 2 (15th December 2019) - Mat Jaafar, Tun N.A.; Taylor, Martin I.; Mohd Nor, Siti A.; Bruyn, Mark de; Carvalho, Gary R.
Abstract: We examine genetic structuring in three commercially important species of the teleost family Carangidae from Malaysian waters: yellowtail scad Atule mate, bigeye scad Selar crumenophthalmus and yellowstripe scad Selaroides leptolepis, from the Indo‐Malay Archipelago. In view of their distribution across contrasting habitats, we tested the hypothesis that pelagic species display less genetic divergence compared with demersal species, due to their potential to undertake long‐distance migrations in oceanic waters. To evaluate population genetic structure, we sequenced two mitochondrial (mt)DNA [650 bp of cytochrome oxidase I ( coI ), 450 bp of control region (CR)] and one nuclear gene (910 bp of rag1 ) in each species. One hundred and eighty samples from four geographical regions within the Indo‐Malay Archipelago including a population of yellowtail from Kuwait were examined. Findings revealed that the extent of genetic structuring among populations in the semi‐pelagic and pelagic, yellowtail and bigeye were lower than demersal yellowstripe, consistent with the hypothesis that pelagic species display less genetic divergence compared with demersal species. The yellowtail phylogeny identified three distinct clades with bootstrap values of 86%–99% in mtDNA and 63%–67% in rag1 . However, in bigeye, three clades were also observed from mtDNA data while only one clade was identified in rag1 dataset. In yellowstripe, the mtDNA tree was split into three closely related clades and two clades in rag1 tree with bootstraps value of 73%–99% and 56% respectively. However, no geographic structure appears in both mtDNA and rag1 datasets. Hierarchical molecular variance analysis (AMOVA), pair wise F ST comparisons and the nearest‐neighbour statistic ( S nn ) showed significant genetic differences among Kuwait and Indo‐Malay yellowtail. Within the Indo‐Malay Archipelago itself, two distinct mitochondrial lineages were detected in yellowtail suggesting potential cryptic species. Findings suggests varying degrees of genetic structuring, key information relevant to management of exploited stocks, though more rapidly evolving genetic markers should be used in future to better delimit the nature and dynamics of putative stock boundaries.